Catholic Church and the Italian public television. An enduring relation with an interlude: the Council - Ruozzi, Federico (Studia Europaea Gnesnensia, 2015)
The article presents the entanglement of the Catholic Church and the media by focusing on the case of the Second Vatican Council and the television broadcast of its events. The mass media attention of the council stimulated, according to the author, a double level: the media conveyed more information about the church event than it had ever done before, but at the same time, the mass media influenced the discussion of the council fathers. The article also analyzes, through the lens of the Council, the recent relationship between the Catholic Church and the Italian television.